Preclinical characterization and phase I clinical trial of CT053PTSA targets MET, AXL, and VEGFR2 in patients with advanced solid tumors - Ma, Yu-Xiang; Liu, Fu-Rong; Zhang, Yang; Chen, Qun; Chen, Zhi-Qiang; Liu, Qian-Wen; Huang, Yan; Yang, Yun-Peng; Fang, Wen-Feng; Xi, Ning; Kang, Ning; Zhuang, Yu-Lei; et al. (Frontiers in Immunology, 2022)
Background: CT053PTSA is a novel tyrosine kinase inhibitor that targets MET, AXL, VEGFR2, FLT3 and MERTK. Here, we present preclinical data about CT053PTSA, and we conducted the first-in-human (FIH) study to evaluate the use of CT053PTSA in adult patients with pretreated advanced solid tumors. Methods: The selectivity and antitumor activity of CT053PTSA were assessed in cell lines in vitro through kinase and cellular screening panels and in cell line-derived tumor xenograft (CDX) and patient-derived xenograft (PDX) models in vivo. The FIH, phase I, single-center, single-arm, dose escalation (3+3 design) study was conducted, patients received at least one dose of CT053PTSA (15 mg QD, 30 mg QD, 60 mg QD, 100 mg QD, and 150 mg QD). The primary objectives were to assess safety and tolerability, to determine the maximum tolerated dose (MTD), dose-limiting toxicity (DLT), and the recommended dose of CT053PTSA for further study. Secondary objectives included pharmacokinetics, antitumor activity. Results: CT053 (free-base form of CT053PTSA) inhibited MET, AXL, VEGFR2, FLT3 and MERTK phosphorylation and suppressed tumor cell angiogenesis by blocking VEGF and HGF, respectively, in vitro. Moreover, cell lines with high MET expression exhibited strong sensitivity to CT053, and CT053 blocked the MET and AXL signaling pathways. In an in vitro study, CT053 significantly inhibited tumor growth in CDX and PDX models. Twenty eligible patients were enrolled in the FIH phase I trial. The most common treatment-related adverse events were transaminase elevation (65%), leukopenia (45%) and neutropenia (35%). DLTs occurred in 3 patients, 1/6 in the 100 mg group and 2/4 in the 150 mg group, so the MTD was set to 100 mg. CT053PTSA was rapidly absorbed after the oral administration of a single dose, and the Cmax and AUC increased proportionally as the dose increased. A total of 17 patients in this trial underwent tumor imaging evaluation, and 29.4% had stable disease. Conclusions: CT053PTSA has potent antitumor and antiangiogenic activity in preclinical models. In this FIH phase I trial, CT053PTSA was well tolerated and had a satisfactory safety profile. Further trials evaluating the clinical activity of CT053PTSA are ongoing.